The Correlation between Students’ Language Awareness and Learning Styles toward Their TOEFL Listening Skill - Aulia Putri (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2017)
The aim of this research was to see the correlation between students’ language awareness and learning styles toward their TOEFL listening skill of English Education Study Program, University of Riau Kepulauan (UNRIKA). This research used quantitative method with correlational research design. The selection of research subject used total sampling of 60 students. Data were collected by using 2 questionnaires for students’ language awareness and learning styles variables, as well as the listening test to measure their TOEFL listening skill. This research was analyzed by using Pearson product moment formula and multiple regression to get multiple correlation coefficient (r). From the results of analysis, it was found that the coefficient of multiple correlation (r) = 0.1763, where r ranged from 0.00 - 0.1999. This meant that there was a very low correlation between language awareness (X1) and learning styles (X2) to the dependent variable of students’ TOEFL listening skill. While the coefficient of determination (r2) = 0.028 which meant that 2.8% variation of the independent variables of language awareness (X1)  and learning styles (X2) can explain the variation of dependent  variable of students’ TOEFL listening skill.